Analisis Manajemen Risiko Teknologi Informasi Penerapan Pada Document Management System di PT. JABAR TELEMATIKA (JATEL) - Gilang Mochammad Husein; Radiant Victor Imbar (Maranatha University Press, 2015)
ADEL (Aplikasi Dokumen Elektronik) and NADINE (Naskah Dinas Elektronik) are the use of information technology (IT) document management system (DMS) electronic archive product that used by JATEL to enhance information quality and to establish an information dan document workflow so it becomes easier, faster, and well-maintained. Electronic archive IT systems are designed to increase the value and benefits of information and able to control the documents distribution and disposition simultaneously that can increase JATEL business value and support business process automation. Information technology can assist organization but also present risks that need to be managed properly. To anticipate or reduce the likelihood of risk, information technology risk management is required. The implementation of information technology risk management involve risk identification, risk assessment and risk treatment.Â Keywords â€” ADEL (Aplikasi Dokumen Elektronik), NADINE (Naskah Dinas Elektronik), risk identification, risk assessment, and risk treatment.